Peranan Pendidikan dalam Menghindari Pergaulan Bebas Anak Usia Remaja di Desa Gunung Rintih Dusun VIII Sidomuncul - Isnaini Ridha Maulida; Winda Sapitri; Feny Rosanti; Sholihah Titin Sumanti (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The educational process is an effort made to develop and facilitate various human potentials. In the world of education, the thing that needs to be studied in depth is the formation of character, because character is a psychological characteristic that can guide to adjust to the environment and avoid promiscuity. The younger generation is a generation that is easily influenced by something in the surrounding environment. Where, the younger generation should begin to learn to assume responsibility and be able to think and act in accordance with the norms prevailing in society. In addition, the low level of education in Indonesia makes the younger generation less knowledgeable about the dangers of promiscuity. When viewed from a sociological perspective, promiscuity is caused by not working well the role and relationship between family, social, and educational institutions towards an individual.